A water-based high-transparency and high-gloss paint applied to protect mirror coating, metallic coating and plating layer and a preparation method thereof
Patent Information
- Application Number
- CN202610897417.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-22
- Publication Date
- 2026-10-30
AI Technical Summary
[0003]1)溶剂型涂料缺陷:含高挥发性有机物(VOC),相对不环保;在施工过程中溶剂会损伤金属感镜面涂层,影响视觉效果
本发明涂料产品通过原料之间的调和协配,共同优化协效,得到的产品性能效果可实现协调式优化改进;
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This invention relates to the field of coating technology, specifically to a water-based high-transmittance, high-gloss coating for use in protective mirror coatings, metallic coatings, and plating layers, and its preparation method. Background Technology
[0002] Metallic mirror coatings or platings are used in industries such as automotive, electronics, home furnishing and building decoration, aerospace and military, and food packaging, providing visual appeal or corrosion resistance and durability to materials such as plastics, glass, cement, and metals. Currently, the topcoats used for metallic mirror coatings and platings are mostly solvent-based or UV (light-cured) coatings, with water-based coatings being less common.
[0003] 1) Defects of solvent-based coatings: They contain high levels of volatile organic compounds (VOCs), making them relatively environmentally unfriendly; during application, the solvents can damage the metallic mirror coating, affecting the visual effect.
[0004] 2) Disadvantages of UV coatings: They have limitations for outdoor use and poor UV resistance; UV monomers can also easily corrode metallic mirror coatings, affecting the visual effect; and their adhesion is generally poor.
[0005] 3) Defects of water-based coatings: low gloss (60° gloss < 80), low light transmittance ( < 85%), affecting visual effect; poor adhesion; poor strength, poor scratch and abrasion resistance. Summary of the Invention
[0006] In view of the deficiencies of the prior art, the purpose of this invention is to provide a water-based high-transmittance, high-gloss coating for use in protective mirror coatings, metallic coatings, and plating layers, and a method for preparing the same, so as to solve the problems mentioned in the background art.
[0007] The present invention solves the technical problem by adopting the following technical solution: This invention provides a water-based high-transmittance, high-gloss coating for use in protective mirror coatings, metallic coatings, and plating layers, comprising the following raw materials in parts by weight: The mixture consists of 45-55 parts silica sol-modified waterborne polyurethane dispersion, 1-2 parts silane coupling agent, 5-10 parts modified nano-alumina dispersion, 0.5-1 part ultraviolet absorber, 0.1-0.3 parts organosilicon leveling agent, 0.3-0.5 parts alkynyl alcohol defoamer, 2-3 parts film-forming aid, 2-3 parts polycarbodiimide crosslinking agent, 3-5 parts functional aid, and 5-10 parts deionized water.
[0008] Preferably, the silane coupling agent is Momentive's Silquest A-186 (β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane); the silicone leveling agent is BYK 3568; the film-forming aid is DPM dipropylene glycol methyl ether; the ultraviolet absorber is BASF Tinuvin 400-DW (N); the alkynol defoamer is Surfynol 107L; and the functional additives are BIT bactericide, polyurethane associative thickener, and citric acid pH adjuster formulated in a weight ratio of 3:2:1.
[0009] The preparation method of the silica sol-modified waterborne polyurethane dispersion is as follows: Preparation of silicate sol: Silicate solution: Dissolve 20g of potassium silicate in 60g of deionized water and stir until completely dissolved; pH adjustment: Slowly add 0.1 M HCl until the solution pH = 8-9; Hydrolysis and condensation: Stir in a 50℃ water bath for 2 hours to form a silica sol; Silane coupling agent (APTES) modified silica sol: APTES pretreatment: Mix 5g APTES with 5g ethanol, add weak acid solution (citric acid, glycine, acetic acid) dropwise to adjust pH=5, pre-hydrolyze for 30 minutes; Grafting reaction: Slowly add the pre-hydrolyzed APTES solution to the silica sol, stir at 60℃ for 4 hours; Silica sol-modified PEG: PEG dispersion: Dissolve 10g PEG-4000 in 20 mL deionized water and heat to 60℃ to dissolve; Blending reaction: Add PEG solution to silane-modified sol and stir at 40℃ for 2 hours to bind through hydrogen bonding or condensation reaction; Dialysis (molecular weight cutoff 3.5 kDa) to remove free PEG and salts; Synthesis of waterborne polyurethane: Polyols are mixed and vacuum dehydrated at 120°C for 2 hours; Cool to 75-80℃, mix HDI (hexamethylene diisocyanate) with polyol (inorganic material with PEG surface modification), react for 2-3 hours to generate -NCO-terminated prepolymer; Add DMPA (2,2-dimethylolpropionic acid) and T12 catalyst (dibutyltin dilaurate), and continue the reaction at 85°C for 2 hours, controlling the -NCO (isocyanate group) content to be 2.5-3.5%; Neutralization: Cool to 40°C, add acetone to reduce viscosity, add triethylamine, and stir for 15 minutes; Emulsification: Deionized water at 5°C is added under high-speed shear (>20m / s), emulsified and dispersed for 15min, modified inorganic material (APTES pretreatment) is added as a chain extender, kept at 50°C for 2 hours, and after deacetone removal, an aqueous polyurethane resin dispersion with a solid content of 30-35% is obtained; the material is discharged through 300-mesh filtration.
[0010] Preferably, the modified nano-alumina dispersion is prepared by: 20nm nano-alumina was preheated at 60-65℃ for 1 hour. The preheated nano-alumina and milling agent were mixed at a weight ratio of 5:3 and ball-milled at 1000 r / min for 2 hours. After ball milling, the mixture was filtered and dried to obtain modified nano-alumina. 5-8 parts of modified nano-alumina, 3-5 parts of chitosan solution and 8-11 parts of sodium dodecylbenzenesulfonate solution were mixed evenly to obtain a modified nano-alumina dispersion.
[0011] Preferably, the chitosan solution has a mass fraction of 2-5%; and the sodium dodecylbenzenesulfonate solution has a mass fraction of 5-8%.
[0012] Preferably, the ball milling agent is prepared by mixing 2-4 parts of nano-titanium oxide, 4-6 parts of lanthanum nitrate solution and 2-5 parts of sodium carboxymethyl cellulose evenly to obtain the ball milling agent.
[0013] Preferably, the lanthanum nitrate solution has a mass fraction of 3-5%.
[0014] A method for preparing a water-based high-transmittance, high-gloss coating for use in protective mirror coatings, metallic coatings, and plating layers includes the following steps: Mix the silane coupling agent and deionized water at 500-800 rpm for 1 hour; then add the modified nano-alumina dispersion, sonicate, then add the waterborne polyurethane resin dispersion, stir and mix evenly at 800-1200 rpm, then add the additives, stir and disperse at 1000-1200 rpm for 30 minutes, then disperse and stir at 300-500 rpm, mature for 1 hour, and filter through a 200-mesh filter.
[0015] Preferably, the ultrasonic power of the ultrasonic treatment is 350-400W, and the ultrasonic treatment lasts for 1 hour.
[0016] Compared with the prior art, the present invention has the following beneficial effects: The coating product of this invention achieves coordinated optimization and improvement of product performance through the blending and synergistic combination of raw materials. Waterborne polyurethane technology principle: By modifying the surface of silicate inorganic materials, on the one hand, their tendency to self-polymerize is reduced, and on the other hand, they can react in situ with polyurethane, further improving the compatibility of materials with different polarities; sufficient carboxyl groups are retained, allowing the resin to form coordination bonds with special silanes in the coating formulation and the substrate, thereby enhancing adhesion.
[0017] The principle of water-based coating technology: Introducing nano-alumina improves coating density and reduces light scattering. Fluorocarbon surfactants reduce surface tension, enhancing the wettability and leveling of low-surface-tension mirror coatings and platings, while optimizing gloss and light transmittance. Special silanes are introduced to strengthen interfacial adhesion and stabilize inorganic materials in the resin and coating formulation. Detailed Implementation
[0018] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to specific examples. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0019] Example 1. This embodiment describes a water-based high-transmittance, high-gloss coating for use in protective mirror coatings, metallic coatings, and plating layers, comprising the following raw materials in parts by weight: The mixture contains 45 parts of silica sol-modified waterborne polyurethane dispersion, 1 part of silane coupling agent, 5 parts of modified nano-alumina dispersion, 0.5 parts of ultraviolet absorber, 0.1 parts of organosilicon leveling agent, 0.3 parts of alkynyl alcohol defoamer, 2 parts of film-forming aid, 2 parts of polycarbodiimide crosslinking agent, 3 parts of functional aid, and 5 parts of deionized water.
[0020] In this embodiment, the silane coupling agent is Momentive's Silquest A-186 (β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane); the silicone leveling agent is BYK 3568; the film-forming aid is DPM dipropylene glycol methyl ether; the ultraviolet absorber is BASF Tinuvin 400-DW (N); the alkynol defoamer is Surfynol 107L; and the functional additives are BIT bactericide, polyurethane associative thickener, and citric acid pH adjuster formulated in a weight ratio of 3:2:1.
[0021] The preparation method of the silica sol-modified waterborne polyurethane dispersion is as follows: Preparation of silicate sol: Silicate solution: Dissolve 20g of potassium silicate in 60g of deionized water and stir until completely dissolved; pH adjustment: Slowly add 0.1 M HCl until the solution pH=8; Hydrolysis and condensation: Stir in a 50℃ water bath for 2 hours to form a silica sol; Silane coupling agent (APTES) modified silica sol: APTES pretreatment: Mix 5g APTES with 5g ethanol, add weak acid solution (citric acid, glycine, acetic acid) dropwise to adjust pH=5, pre-hydrolyze for 30 minutes; Grafting reaction: Slowly add the pre-hydrolyzed APTES solution to the silica sol, stir at 60℃ for 4 hours; Silica sol-modified PEG: PEG dispersion: Dissolve 10g PEG-4000 in 20 mL deionized water and heat to 60℃ to dissolve; Blending reaction: Add PEG solution to silane-modified sol and stir at 40℃ for 2 hours to bind through hydrogen bonding or condensation reaction; Dialysis (molecular weight cutoff 3.5 kDa) to remove free PEG and salts; Synthesis of waterborne polyurethane: Polyols are mixed and vacuum dehydrated at 120°C for 2 hours; Cool the mixture to 75-80℃, mix HDI with polyol (containing inorganic materials with PEG surface modification), and react for 2-3 hours to generate -NCO-terminated prepolymer; Add DMPA and T12 catalyst, and continue the reaction at 85°C for 2 hours, controlling the -NCO content to 2.5%; Neutralization: Cool to 40°C, add acetone to reduce viscosity, add triethylamine, and stir for 15 minutes; Emulsification: Deionized water at 5°C was added under high-speed shear (>20m / s), and the mixture was emulsified and dispersed for 15 minutes. Modified inorganic material (pretreated with APTES) was added as a chain extender, and the mixture was kept at 50°C for 2 hours. After deacetone removal, a waterborne polyurethane resin dispersion with a solid content of 30% was obtained. The mixture was then filtered through a 300-mesh filter.
[0022] The preparation method of the modified nano-alumina dispersion is as follows: 20nm nano-alumina was preheated at 60℃ for 1 hour. The preheated nano-alumina and milling agent were mixed at a weight ratio of 5:3 and ball-milled at 1000 r / min for 2 hours. After ball milling, the mixture was filtered and dried to obtain modified nano-alumina. 5 parts of modified nano-alumina, 3 parts of chitosan solution and 8 parts of sodium dodecylbenzenesulfonate solution were mixed evenly to obtain a modified nano-alumina dispersion.
[0023] In this embodiment, the chitosan solution has a mass fraction of 2%; the sodium dodecylbenzenesulfonate solution has a mass fraction of 5%.
[0024] The preparation method of the ball milling agent in this embodiment is as follows: 2 parts of nano titanium dioxide, 4 parts of lanthanum nitrate solution and 2 parts of sodium carboxymethyl cellulose are mixed evenly to obtain the ball milling agent.
[0025] The lanthanum nitrate solution in this embodiment has a mass fraction of 3%.
[0026] A method for preparing a water-based high-transmittance, high-gloss coating for use in protective mirror coatings, metallic coatings, and plating layers includes the following steps: Mix the silane coupling agent and deionized water at 500 rpm for 1 hour; then add the modified nano alumina dispersion, sonicate, then add the waterborne polyurethane resin dispersion, stir at 800 rpm until uniform, then add the additives, stir at 1000 rpm for 30 minutes, then disperse at 300 rpm, mature for 1 hour, and filter through a 200-mesh filter.
[0027] In this embodiment, the ultrasonic power for ultrasonic treatment is 350W, and the ultrasonic treatment lasts for 1 hour.
[0028] The wet film thickness of the topcoat is 25μm.
[0029] Example 2. This embodiment describes a water-based high-transmittance, high-gloss coating for use in protective mirror coatings, metallic coatings, and plating layers, comprising the following raw materials in parts by weight: The mixture contains 55 parts of silica sol-modified waterborne polyurethane dispersion, 2 parts of silane coupling agent, 10 parts of modified nano-alumina dispersion, 1 part of ultraviolet absorber, 0.3 parts of organosilicon leveling agent, 0.5 parts of alkynyl alcohol defoamer, 3 parts of film-forming aid, 3 parts of polycarbodiimide crosslinking agent, 5 parts of functional aid, and 10 parts of deionized water.
[0030] In this embodiment, the silane coupling agent is Momentive's Silquest A-186 (β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane); the silicone leveling agent is BYK 3568; the film-forming aid is DPM dipropylene glycol methyl ether; the ultraviolet absorber is BASF Tinuvin 400-DW (N); the alkynol defoamer is Surfynol 107L; and the functional additives are BIT bactericide, polyurethane associative thickener, and citric acid pH adjuster formulated in a weight ratio of 3:2:1.
[0031] The preparation method of the silica sol-modified waterborne polyurethane dispersion is as follows: Preparation of silicate sol: Silicate solution: Dissolve 20g of potassium silicate in 60g of deionized water and stir until completely dissolved; pH adjustment: Slowly add 0.1 M HCl until the solution pH = 8-9; Hydrolysis and condensation: Stir in a 50℃ water bath for 2 hours to form a silica sol; Silane coupling agent (APTES) modified silica sol: APTES pretreatment: Mix 5g APTES with 5g ethanol, add weak acid solution (citric acid, glycine, acetic acid) dropwise to adjust pH=5, pre-hydrolyze for 30 minutes; Grafting reaction: Slowly add the pre-hydrolyzed APTES solution to the silica sol, stir at 60℃ for 4 hours; Silica sol-modified PEG: PEG dispersion: Dissolve 10g PEG-4000 in 20 mL deionized water and heat to 60℃ to dissolve; Blending reaction: Add PEG solution to silane-modified sol and stir at 40℃ for 2 hours to bind through hydrogen bonding or condensation reaction; Dialysis (molecular weight cutoff 3.5 kDa) to remove free PEG and salts; Synthesis of waterborne polyurethane: Polyols are mixed and vacuum dehydrated at 120°C for 2 hours; The mixture was cooled to 78°C and mixed with a polyol (containing an inorganic material with PEG surface modification). The mixture was reacted for 3 hours to generate an -NCO-terminated prepolymer. Add DMPA and T12 catalyst, and continue the reaction at 85°C for 2 hours, controlling the -NCO content to 3.5%; Neutralization: Cool to 40°C, add acetone to reduce viscosity, add triethylamine, and stir for 15 minutes; Emulsification: Deionized water at 5°C was added under high-speed shear (>20m / s), and the mixture was emulsified and dispersed for 15 minutes. Modified inorganic material (pretreated with APTES) was added as a chain extender, and the mixture was kept at 50°C for 2 hours. After deacetone removal, an aqueous polyurethane resin dispersion with a solid content of 35% was obtained. The mixture was then filtered through a 300-mesh filter.
[0032] The preparation method of the modified nano-alumina dispersion is as follows: 20nm nano-alumina was preheated at 65℃ for 1 hour. The preheated nano-alumina and milling agent were mixed at a weight ratio of 5:3 and ball-milled at 1000 r / min for 2 hours. After ball milling, the mixture was filtered and dried to obtain modified nano-alumina. 8 parts of modified nano-alumina, 5 parts of chitosan solution and 11 parts of sodium dodecylbenzenesulfonate solution were mixed evenly to obtain a modified nano-alumina dispersion.
[0033] In this embodiment, the chitosan solution has a mass fraction of 5%; the sodium dodecylbenzenesulfonate solution has a mass fraction of 8%.
[0034] The preparation method of the ball milling agent in this embodiment is as follows: 4 parts of nano titanium dioxide, 6 parts of lanthanum nitrate solution and 5 parts of sodium carboxymethyl cellulose are mixed evenly to obtain the ball milling agent.
[0035] The lanthanum nitrate solution in this embodiment has a mass fraction of 5%.
[0036] A method for preparing a water-based high-transmittance, high-gloss coating for use in protective mirror coatings, metallic coatings, and plating layers includes the following steps: Mix the silane coupling agent and deionized water at 800 rpm for 1 hour; then add the modified nano alumina dispersion, sonicate, then add the waterborne polyurethane resin dispersion, stir and mix evenly at 1200 rpm, then add the additives, stir and disperse at 1200 rpm for 30 minutes, then disperse and stir at 500 rpm, mature for 1 hour, and filter through a 200-mesh filter.
[0037] In this embodiment, the ultrasonic power for ultrasonic treatment is 400W, and the ultrasonic treatment lasts for 1 hour. The wet film thickness of the topcoat is 25μm.
[0038] Example 3. This embodiment describes a water-based high-transmittance, high-gloss coating for use in protective mirror coatings, metallic coatings, and plating layers, comprising the following raw materials in parts by weight: The mixture contains 50 parts of silica sol-modified waterborne polyurethane dispersion, 1.5 parts of silane coupling agent, 7.5 parts of modified nano-alumina dispersion, 0.75 parts of ultraviolet absorber, 0.2 parts of organosilicon leveling agent, 0.4 parts of alkynyl alcohol defoamer, 2.5 parts of film-forming aid, 2.5 parts of polycarbodiimide crosslinking agent, 4 parts of functional aid, and 7.5 parts of deionized water.
[0039] In this embodiment, the silane coupling agent is Momentive's Silquest A-186 (β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane); the silicone leveling agent is BYK 3568; the film-forming aid is DPM dipropylene glycol methyl ether; the ultraviolet absorber is BASF Tinuvin 400-DW (N); the alkynol defoamer is Surfynol 107L; and the functional additives are BIT bactericide, polyurethane associative thickener, and citric acid pH adjuster formulated in a weight ratio of 3:2:1.
[0040] In this embodiment, the silane coupling agent is silane coupling agent KH560; the fluorine-modified wetting and leveling agent is fluorine-modified acrylic leveling agent; the film-forming aid is ethylene glycol butyl ether acetate; the ultraviolet absorber is BASF UV-328; and the silicone defoamer is DF-295.
[0041] The preparation method of the silica sol-modified waterborne polyurethane dispersion is as follows: Preparation of silicate sol: Silicate solution: Dissolve 20g of potassium silicate in 60g of deionized water and stir until completely dissolved; pH adjustment: Slowly add 0.1 M HCl until the solution pH=8.5; Hydrolysis and condensation: Stir in a 50℃ water bath for 2 hours to form a silica sol; Silane coupling agent (APTES) modified silica sol: APTES pretreatment: Mix 5g APTES with 5g ethanol, add weak acid solution (citric acid, glycine, acetic acid) dropwise to adjust pH=5, pre-hydrolyze for 30 minutes; Grafting reaction: Slowly add the pre-hydrolyzed APTES solution to the silica sol, stir at 60℃ for 4 hours; Silica sol-modified PEG: PEG dispersion: Dissolve 10g PEG-4000 in 20 mL deionized water and heat to 60℃ to dissolve; Blending reaction: Add PEG solution to silane-modified sol and stir at 40℃ for 2 hours to bind through hydrogen bonding or condensation reaction; Dialysis (molecular weight cutoff 3.5 kDa) to remove free PEG and salts; Synthesis of waterborne polyurethane: Polyols are mixed and vacuum dehydrated at 120°C for 2 hours; The mixture was cooled to 78°C and mixed with a polyol (containing an inorganic material with PEG surface modification). The mixture was reacted for 2.5 hours to generate an -NCO-terminated prepolymer. Add DMPA and T12 catalyst, and continue the reaction at 85°C for 2 hours, controlling the -NCO content to 3.0%. Neutralization: Cool to 40°C, add acetone to reduce viscosity, add triethylamine, and stir for 15 minutes; Emulsification: Deionized water at 5°C was added under high-speed shear (>20m / s), and the mixture was emulsified and dispersed for 15 minutes. Modified inorganic material (pretreated with APTES) was added as a chain extender, and the mixture was kept at 50°C for 2 hours. After deacetone removal, an aqueous polyurethane resin dispersion with a solid content of 32.5% was obtained. The mixture was then filtered through a 300-mesh filter.
[0042] Preferably, the modified nano-alumina dispersion is prepared by: 20nm nano-alumina was preheated at 62.5℃ for 1 hour. The preheated nano-alumina and milling agent were mixed at a weight ratio of 5:3 and ball-milled at 1000 r / min for 2 hours. After ball milling, the mixture was filtered and dried to obtain modified nano-alumina. 6.5 parts of modified nano-alumina, 4 parts of chitosan solution and 9 parts of sodium dodecylbenzenesulfonate solution were mixed evenly to obtain a modified nano-alumina dispersion.
[0043] In this embodiment, the chitosan solution has a mass fraction of 3.5%; the sodium dodecylbenzenesulfonate solution has a mass fraction of 6.5%.
[0044] The preparation method of the ball milling agent in this embodiment is as follows: 3 parts of nano titanium dioxide, 5 parts of lanthanum nitrate solution and 3.5 parts of sodium carboxymethyl cellulose are mixed evenly to obtain the ball milling agent.
[0045] The mass fraction of the lanthanum nitrate solution in this embodiment is 4%.
[0046] A method for preparing a water-based high-transmittance, high-gloss coating for use in protective mirror coatings, metallic coatings, and plating layers includes the following steps: Mix the silane coupling agent and deionized water at 650 rpm for 1 hour; then add the modified nano alumina dispersion, sonicate, then add the waterborne polyurethane resin dispersion, stir at 1000 rpm until uniform, then add the additives, stir at 1100 rpm for 30 minutes, then disperse at 400 rpm, mature for 1 hour, and filter through a 200-mesh filter.
[0047] In this embodiment, the ultrasonic power for ultrasonic treatment is 370W, and the ultrasonic treatment lasts for 1 hour. The wet film thickness of the topcoat is 25μm.
[0048] The product performance of Examples 1-3 and the performance tests of Comparative Examples 1-3 are as follows: Comparative Example 1. Unlike Example 3, no ball milling agent was added in the preparation of the modified nano alumina dispersion.
[0049] Comparative Example 2. Unlike Example 3, nano-titanium oxide and sodium carboxymethyl cellulose were not added to the ball milling agent.
[0050] Comparative Example 3. Unlike Example 3, the lanthanum nitrate solution was replaced with water.
[0051] Comparative Example 4. Unlike Example 3, a commercially available nano-alumina dispersion was added to the coating.
[0052] Comparative Example 5. Unlike Example 3, the paint formulation ratio remains the same, and the topcoat spraying thickness is 55μm.
[0053] Test specimens and construction process compilation Test piece 1 Substrate: LG 50μm optical grade PET film (transmittance ≥91.5%, haze ≤1.2%) Construction process: Spray a water-based high-transparency, high-gloss mirror topcoat with a wet film thickness of 20–30 μm and dry at 90℃ for 15 min.
[0054] Overall curing of the workpiece: 60℃, 24h.
[0055]
[0056] Test piece two Substrate: Mirror silver plated (aluminum plated) plastic workpiece. Construction process: Spray a water-based high-transparency, high-gloss mirror topcoat with a wet film thickness of 20–30 μm and dry at 90℃ for 15 min.
[0057] Overall curing of the workpiece: 60℃, 24h.
[0058]
[0059]
[0060]
[0061] Test piece three Substrate: Standard black ABS test board Construction process: 1. Spray a water-based two-component transparent primer to a wet film thickness of 20–30 μm and dry at 80°C for 15 min. 2.1. Spray a thin layer of water-based mirror silver (aluminum silver paste) intermediate coat and dry at 90°C for 20 min.
[0062] 2-2. Apply a thin layer of oil-based mirror silver (aluminum silver paste) intermediate coating and dry at 90℃ for 20 minutes.
[0063] 2-3. Apply a thin, oil-based nano-silver mirror coating (nano-silver paste) as the intermediate coat and dry at 120℃ for 20 minutes.
[0064] Spray a water-based high-transparency, high-gloss mirror topcoat with a wet film thickness of 20–30 μm and dry at 90℃ for 15 min.
[0065] Overall curing of the workpiece: 60℃, 24h.
[0066]
[0067]
[0068]
[0069]
[0070] Test piece four Substrate: Black ABS 30cm car model (with curved surface) Construction process: Apply a water-based two-component clear primer to a wet film thickness of 20–30 μm and dry at 80°C for 15 minutes. 3-1. Apply a thin layer of water-based mirror silver (aluminum silver paste) intermediate coating and dry at 90℃ for 20 minutes.
[0071] 3-2. Apply a thin layer of oil-based mirror silver (aluminum silver paste) intermediate coating and dry at 90℃ for 20 minutes.
[0072] 3-3. Apply a thin spray of oil-based nano-silver mirror coating (nano-silver paste) as the intermediate coat, and dry at 120℃ for 20 minutes.
[0073] Spray a water-based high-transparency, high-gloss mirror topcoat with a wet film thickness of 20–30 μm and dry at 90℃ for 15 min.
[0074] Overall curing of the workpiece: 60℃, 24h.
[0075] To test the gloss ①, on a standard black ABS sheet, first spray a primer, then spray a water-based mirror silver (aluminum silver paste) coating, and then spray the invented coating.
[0076] Test Guan Ze②: On a standard black ABS sheet, first spray a primer, then spray an oil-based nano-silver mirror coating (nano-silver paste), and finally spray the invented coating. To test adhesion ①, on a standard black ABS sheet, first spray a primer, then spray a water-based mirror silver (aluminum silver paste) coating, and then spray the invented coating.
[0077] Adhesion test ②: On a standard black ABS sheet, first spray a primer, then spray an oil-based nano-silver mirror coating (nano-silver paste), and then spray the invented coating.
[0078] Adhesion test ③: On a standard black ABS sheet, a mirror silver (aluminum) coating is applied, followed by spraying the invented coating.
[0079] For the water resistance test, a primer was first sprayed onto a standard black ABS sheet, followed by a water-based mirror silver (aluminum silver paste) coating, and then the invented coating.
[0080] For the water resistance test, a primer was first sprayed onto a standard black ABS sheet, followed by an oil-based mirror silver (aluminum silver paste) coating, and then the invention coating.
[0081] For the water resistance test, a primer was first sprayed onto a standard black ABS sheet, followed by a water-based mirror silver (aluminum silver paste) coating, and then the invention coating.
[0082] Mirror effect (visual assessment): On a standard black ABS sheet, a primer was first sprayed, then an oil-based nano-silver mirror coating (nano-silver paste) was sprayed, and finally the invented coating was sprayed. The test results are as follows:
[0083]
[0084]
[0085] Through the above measurements of different processes and procedures, it is demonstrated that the products of Examples 1-3 of the present invention have excellent performance and significant performance stability, while the products of Comparative Examples 1-5 are not as effective as the products of the present invention.
[0086] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above, and that the invention can be implemented in other specific forms without departing from the spirit or essential characteristics of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description. Thus, it is intended that all variations falling within the meaning and scope of equivalents of the claims be included within the present invention.
[0087] Furthermore, it should be understood that although this specification describes embodiments, not every embodiment contains only one independent technical solution. This narrative style is merely for clarity. Those skilled in the art should consider the specification as a whole, and the technical solutions in each embodiment can also be appropriately combined to form other embodiments that can be understood by those skilled in the art.
Claims
1. A water-based high-transmittance, high-gloss coating for use in protective mirror coatings, metallic coatings, and plating layers, characterized in that, Including the following parts by weight of raw materials: The mixture consists of 45-55 parts silica sol-modified waterborne polyurethane dispersion, 1-2 parts silane coupling agent, 5-10 parts modified nano-alumina dispersion, 0.5-1 part ultraviolet absorber, 0.1-0.3 parts organosilicon leveling agent, 0.3-0.5 parts alkynyl alcohol defoamer, 2-3 parts film-forming aid, 2-3 parts polycarbodiimide crosslinking agent, 3-5 parts functional aid, and 5-10 parts deionized water.
2. The water-based high-transmittance, high-gloss coating for use in protective mirror coatings, metallic coatings, and platings according to claim 1, characterized in that, The silane coupling agent is Momentive's Silquest A-186 (β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane); the silicone leveling agent is BYK 3568; the film-forming aid is DPM dipropylene glycol methyl ether; the ultraviolet absorber is BASF Tinuvin 400-DW (N); the alkynol defoamer is Surfynol 107L; and the functional additives are BIT bactericide, polyurethane associative thickener, and citric acid pH adjuster formulated in a weight ratio of 3:2:
1.
3. The water-based high-transmittance, high-gloss coating for use in protective mirror coatings, metallic coatings, and platings according to claim 1, characterized in that, The preparation method of the silica sol-modified waterborne polyurethane dispersion is as follows: Preparation of silicate sol: Silicate solution: Dissolve 20g of potassium silicate in 60g of deionized water and stir until completely dissolved; pH adjustment: Slowly add 0.1 M HCl until the solution pH = 8-9; Hydrolysis and condensation: Stir in a 50℃ water bath for 2 hours to form a silica sol; Silane coupling agent (APTES) modified silica sol: APTES pretreatment: Mix 5g APTES with 5g ethanol, add weak acid solution (citric acid, glycine, acetic acid) dropwise to adjust pH=5, pre-hydrolyze for 30 minutes; Grafting reaction: Slowly add the pre-hydrolyzed APTES solution to the silica sol, stir at 60℃ for 4 hours; Silica sol-modified PEG: PEG dispersion: Dissolve 10g PEG-4000 in 20 mL deionized water and heat to 60℃ to dissolve; Blending reaction: Add PEG solution to silane-modified sol and stir at 40℃ for 2 hours to bind through hydrogen bonding or condensation reaction; Dialysis (molecular weight cutoff 3.5 kDa) to remove free PEG and salts; Synthesis of waterborne polyurethane: Polyols are mixed and vacuum dehydrated at 120°C for 2 hours; Cool the mixture to 75-80℃, mix HDI with polyol (containing inorganic materials with PEG surface modification), and react for 2-3 hours to generate -NCO-terminated prepolymer; Add DMPA and T12 catalyst, and continue the reaction at 85°C for 2 hours, controlling the -NCO content to be 2.5-3.5%. Neutralization: Cool to 40°C, add acetone to reduce viscosity, add triethylamine, and stir for 15 minutes; Emulsification: Deionized water at 5°C is added under high-speed shear (>20m / s), emulsified and dispersed for 15min, modified inorganic material (APTES pretreatment) is added as a chain extender, kept at 50°C for 2 hours, and after deacetone removal, an aqueous polyurethane resin dispersion with a solid content of 30-35% is obtained; the material is discharged through 300-mesh filtration.
4. The water-based high-transmittance, high-gloss coating for use in protective mirror coatings, metallic coatings, and platings according to claim 1, characterized in that, The preparation method of the modified nano-alumina dispersion is as follows: 20nm nano-alumina was preheated at 60-65℃ for 1 hour. The preheated nano-alumina and milling agent were mixed at a weight ratio of 5:3 and ball-milled at 1000 r / min for 2 hours. After ball milling, the mixture was filtered and dried to obtain modified nano-alumina. 5-8 parts of modified nano-alumina, 3-5 parts of chitosan solution and 8-11 parts of sodium dodecylbenzenesulfonate solution were mixed evenly to obtain a modified nano-alumina dispersion.
5. The water-based high-transmittance, high-gloss coating for use in protective mirror coatings, metallic coatings, and platings according to claim 4, characterized in that, The chitosan solution has a mass fraction of 2-5%; the sodium dodecylbenzenesulfonate solution has a mass fraction of 5-8%.
6. The water-based high-transmittance, high-gloss coating for use in protective mirror coatings, metallic coatings, and platings according to claim 5, characterized in that, The ball milling agent is prepared by mixing 2-4 parts of nano-titanium oxide, 4-6 parts of lanthanum nitrate solution and 2-5 parts of sodium carboxymethyl cellulose evenly to obtain the ball milling agent.
7. The water-based high-transmittance, high-gloss coating for use in protective mirror coatings, metallic coatings, and platings according to claim 6, characterized in that, The lanthanum nitrate solution has a mass fraction of 3-5%.
8. A method for preparing a water-based high-transmittance, high-gloss coating for use in protective mirror coatings, metallic coatings, and platings, as described in any one of claims 1-7, characterized in that... Includes the following steps: Mix the silane coupling agent and deionized water at 500-800 rpm for 1 hour; then add the modified nano-alumina dispersion, sonicate, then add the waterborne polyurethane resin dispersion, stir and mix evenly at 800-1200 rpm, then add the additives, stir and disperse at 1000-1200 rpm for 30 minutes, then disperse and stir at 300-500 rpm, mature for 1 hour, and filter through a 200-mesh filter.
9. The method for preparing a water-based high-transmittance, high-gloss coating for use in protective mirror coatings, metallic coatings, and plating as described in claim 8, characterized in that, The ultrasonic power of the ultrasonic treatment is 350-400W, and the ultrasonic treatment lasts for 1 hour.
